PENERAPAN MODEL PEMBELAJARAN JIGSAW DALAM MENINGKATKAN MINAT BELAJAR SISWA SMK MUHAMMADIYAH 2 PEKANBARU - Putri Clawson; Ahmad Nasirudin (P3M STKIP 'Aisyiyah Riau, 2020)
ABSTRACT The purpose of this study is to study the increase in student learning interest among students who study using the jigsaw cooperative learning model with students whose learning does not use a jigsaw cooperative learning model in class XII entrepreneurship learning in SMK Muhammadiyah 02 Pekanbaru. This research was conducted at SMK Muhammadiyah 02 Pekanbaru. The method used in this study is a quasi research method with 72 students of class XII TKJ at SMK Muhammadiyah 02 Pekanbaru. The object of this research is class XII TKJ 1 as a control class and class XII TKJ 2 as an experimental class. Data collection tools in this study with a questionnaire, data analysis techniques used are t-test analysis. Jigsaw type cooperative learning research model has a positive impact on student learning interest. This is indicated by the average value of the experimental posttest class is higher than the average value of the posttest control class. The experimental value received an average posttest value of 69.361 while for the control class of 66.861. From the results of the analysis of the hypothesis test conducted, there are differences in student learning interest between students who learn to use the Jigsaw type cooperative learning model and students whose learning does not use the Jigsaw type cooperative learning model.